Biblioteche private nella Sardegna del Seicento - Usalla, Laura (Libri e biblioteche in Sardegna, 2020)
This volume is the result of an extensive archival research, and contains the analysis of 120 notarial documents useful for the reconstruction of seventeenth-century Sardinian private libraries. These are mainly post-mortem inventories through which it is possible to detect the consistency and characteristics of the library collections in use by people of different social backgrounds and professional roles. The collected materials make the repertory a valuable tool for scholars of book history and cultural history.